A viaduct for Madrid. The infrastructure project of Agustín Aguirre - Amarouch García, Ismael (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
The Modern Movement in Spain was received in 1928, according to historians. It met with some resistance among the architects of the Madrid group, who were willing to accept the renewal of the style if it was oriented towards solving problems in a natural way. One of the most talented architects of that generation was Agustín Aguirre. He was someone who, throughout his career and due to various circumstances, did not make the most of his gifts as a draughtsman. His most important work, the Faculty of Philosophy and Letters, coincided with the years of the Second Spanish Republic, probably when his contact with the avant-garde was most intense, both through his travels abroad and through his reading of publications. In 1932, while the final design for the Faculty was being drawn up, Aguirre took part, together with the engineer Rafael Ceballos, in the competition to rebuild the Madrid viaduct over Segovia Street. It was an unpublished project with a special sensitivity for combining monumentality and practical utility, which this article will attempt to explain from three future perspectives: city-scale building, informed matter and coherence. Road infrastructure as such is a territorial interference, but this concept would be amplified by the ephemeral resonance of the avant-garde and interdisciplinary collaboration.
Keywords: Agustín Aguirre; European avant-garde; modern Spanish architecture; Madrid’s 1925 Generation; viaduct